Normative Juridical Study on the Second Amendment to Law Number 6 of 2014 on Villages in Law Number 3 of 2024: The Implications for Enhancing Village Independence in Indonesia. - Deddy Winarwan; Thea Farina; Ivans Januardy (Dinasti Research, 2025)
Law Number 6 of 2014 concerning Villages aims to increase village independence. However, changes in Law Number 3 of 2024 raise questions about whether this new regulation strengthens or weakens village independence. This study aims to identify articles that impact village independence and assess their implications through a comparative and logical approach. The analysis was conducted using a normative legal method and responsive legal theory. The study results show that seven articles in Law Number 3 of 2024 affect village independence. Five articles have a negative impact, while two new articles (Articles 72A and 87A) have a positive effect. The decline in village independence occurs due to budget dependence on the central and regional governments (Articles 72 and 74), reduced transparency (Article 86), and external intervention in village development (Articles 67 and 78). In contrast, Article 72A clarifies the use of the village budget, and Article 87A strengthens the role of BUMDes as a pillar of the village economy. Overall, Law Number 3 of 2024 will reduce rather than increase village independence, thus potentially hindering villages from achieving better welfare.